Electromagnetic Testing and Failure Prediction of Antenna Systems Using Intelligent Technologies - Bondarchuk, Viktor; Matsui, Anatolii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
У статті виконано аналіз основних технологій сучасних бездротових телекомунікацій, що зумовлюють трансформацію методів електромагнітного тестування та діагностики радіочастотних компонентів. Особливу увагу приділено післявиробничим OTA-методам, які забезпечують неінвазійний контроль активних антенних систем у реальних умовах експлуатації. Розглянуто можливості інтеграції інтелектуальних алгоритмів, зокрема методів машинного навчання та глибинних нейронних мереж, як засобу підвищення ефективності виявлення дефектів і побудови моделей прогнозування відмов на основі аналізу великих обсягів вимірювальних даних. The paper analyzes the core technologies of modern wireless telecommunications that necessitate a transformation of electromagnetic testing and diagnostic methodologies for radio-frequency components. Special attention is given to post-production OTA methods enabling non-invasive evaluation of active antenna systems under realistic operating conditions. The integration of intelligent algorithms, including machine learning and deep neural networks, is examined as a means of improving defect detection efficiency and developing predictive failure models based on large-scale measurement data analysis.